An eye tracking system for monitoring face scanning patterns reveals the enhancing effect of oxytocin on eye contact in common marmosets. (September 2017) - Kotani, Manato; Shimono, Kohei; Yoneyama, Toshihiro; Nakako, Tomokazu; Matsumoto, Kenji; Ogi, Yuji; Konoike, Naho; Nakamura, Katsuki; Ikeda, Kazuhito
Highlights: A newly established method for eye tracking in common marmosets was developed. Face scanning patterns in common marmosets were characterized. Oxytocin significantly enhanced the change in eyes/face ratio compared to the vehicle condition. L-368, 899, an oxytocin receptor antagonist, completely blocked oxytocin - induced increase in the change in eyes/face ratio. Abstract: Eye tracking systems are used to investigate eyes position and gaze patterns presumed as eye contact in humans. Eye contact is a useful biomarker of social communication and known to be deficient in patients with autism spectrum disorders (ASDs). Interestingly, the same eye tracking systems have been used to directly compare face scanning patterns in some non-human primates to those in human. Thus, eye tracking is expected to be a useful translational technique for investigating not only social attention and visual interest, but also the effects of psychiatric drugs, such as oxytocin, a neuropeptide that regulates social behavior. In this study, we report on a newly established method for eye tracking in common marmosets as unique New World primates that, like humans, use eye contact as a mean of communication. Our investigation was aimed at characterizing these primates face scanning patterns and evaluating the effects of oxytocin on their eye contact behavior. We found that normal common marmosets spend more time viewing the eyes region in common marmoset's picture than the mouth region or a scrambled picture. In oxytocin experiment, the change in eyes/face ratio was significantly greater in the oxytocin group than in the vehicle group. Moreover, oxytocin-induced increase in the change in eyes/face ratio was completely blocked by the oxytocin receptor antagonist L-368, 899. These results indicate that eye tracking in common marmosets may be useful for evaluating drug candidates targeting psychiatric conditions, especially ASDs.